(untitled) (Research, Society and Development, 2023)
The gastroesophageal reflux disease (GERD) represents a high rate prevalence in most people of the world, their symptoms are frequent in clinical practice. The pharmacological treatment is the most widely used, although has a high recurrence of symptoms and low resolution rate, encouraging the search for another types of treatments. The purpose of this study was to present alternative treatments and stimulate their use. It’s an integrative review search carried out through in PubMed, Scielo and Google Scholar databases, including the search`s descriptors and the following criteria: free full text, clinical trial, randomized controlled trial, articles published in the last two years. Thereby, there is a necessity to complement the treatment through another management, like the lifestyle interventions and phytotherapy, getting more and long-time benefits.